Evaluating Stock Status of 16 Commercial Fish Species in the Coastal and Offshore Waters of Taiwan Using the CMSY and BSM Methods - Ju, Peilong; Tian, Yongjun; Chen, Mingru; Yang, Shengyun; Liu, Yang; Xing, Qinwang; Sun, Peng (Frontiers in Marine Science, 2020)
The waters around Taiwan are impacted by the Kuroshio and coastal currents, resulting in a high productivity and a high diversity of marine life. As a consequence, there are a multitude of fisheries around Taiwan, conducted by a fleet that has grown enormously in the last four decades. Here, we investigate the effect of the resulting fishing pressure on 16 commercial fish stocks including demersal and pelagic species in the coastal and offshore waters of Taiwan using the Monte Carlo Catch-Maximum Sustainable Yield (CMSY) and Bayesian Schaefer Model (BSM) methods. Both of these methods required principally catch time series, with the BSM methods also requiring catch-per-unit-of-effort data. The results show that of the 16 assessed stocks, 10 stocks have collapsed, 2 are severely overfished, 2 are overfished, 1 is slightly overfished, and only 1 stock remains in a healthy status; these troubling results are attributed to excessive fishing pressure. However, climate-driven environmental variability may be another factor affecting the fishery resources around Taiwan, as evidenced by chub mackerel Scomber japonicus, the one stock deemed healthy, which is here attributed to favorable environmental condition. Using the fisheries reference points provided here, rebuilding plans could be provided for the other 15 species; however, such plans are not likely to be successful without reducing the size of the Taiwanese fishing fleet.